2020
DOI: 10.1002/ange.202006318
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Au−C≡C Functionalized Surface: Toward Real‐Time Mapping and Accurate Quantification of Fe2+ in the Brains of Live AD Mouse Models

Abstract: Described here is that AuÀCCb onds showed the highest stability under biological conditions,w ith abundant thiols,a nd the best electrochemical performance compared to Au À Sand Au À Se bonds.The new finding was also confirmed by theorical calculations.B ased on this finding, as pecific molecule for recognition of Fe 2+ was designed and synthesized, and used to create as elective and accurate electrochemical sensor for the quantification of Fe 2+ .T he present ratiometric strategy demonstrates high spatial res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…In spite of the intense research interest in the Au–C bonding on Au surfaces, direct experimental evidence of its existence is still missing to support the calculations of its nature. 22 , 23 X-ray photoelectron spectroscopy (XPS) is typically applied to investigate interactions for modified metal surfaces, including Au. Laforgue et al.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the intense research interest in the Au–C bonding on Au surfaces, direct experimental evidence of its existence is still missing to support the calculations of its nature. 22 , 23 X-ray photoelectron spectroscopy (XPS) is typically applied to investigate interactions for modified metal surfaces, including Au. Laforgue et al.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the synthesized AuNCs displayed a board absorption and apparent TPF emission around 540 nm (Supporting information Figure S10). Then, a ratiometric TPF probe was assembled by conjugating RBD onto AuNCs through robust Au-COC bond, 35 named as RBD@AuNCs. Fourier transform infrared spectrometer (FT-IR) spectrum of RBD@AuNCs exhibited the disappearance of typical vibration peaks of O (3293 cm -1 ) and O $!…”
Section: Resultsmentioning
confidence: 99%
“…Over the past few years, several articles have considered ratiometric sensors for use in in vivo measurement [ 119 , 120 , 121 , 122 ]. The first study demonstrated changes in pH and compared the quantity of copper ions in normal and Alzheimer’s disease (AD) rats [ 119 ].…”
Section: In Vivo Applications Of Nano- and Microelectrodes In Biologi...mentioning
confidence: 99%
“…Other metal ions are also involved in the processes of neurodegenerative diseases. Zhang et al presented a ratiometric electrochemical sensor based on a Au−C≡C bond surface for real-time mapping and accurate quantification of Fe 2+ in the brains of a live AD mouse [ 122 ]. The author used a carbon CF microelectrode as a base followed by gold precipitation on the electrode surface.…”
Section: In Vivo Applications Of Nano- and Microelectrodes In Biologi...mentioning
confidence: 99%